Improving asthma severity and control screening in a primary care pediatric practice. Issue 1 (25th February 2016) - Sudhanthar, Sathyanarayan; Turner, Jane; Sigal, Yakov; Thakur, Kripa; Gold, Jonathan
Abstract: Asthma is the most commonly encountered chronic disease in children. Periodic assessment of asthma severity and control is an integral part of asthma management, but patients with uncontrolled asthma don't always schedule routine asthma care visits. The aim of this project was to improve asthma control and severity screening in a primary care setting by using a validated tool for all visits for patients with a diagnosis of asthma aged 4-21 years. Our QI team developed a protocol to administer the Asthma Control Test (TM), a validated questionnaire to assess asthma control. The stakeholders involved were the physicians, nursing staff, and the Health Information Team (HIT). All patients who had a prior diagnosis of asthma or with an asthma medication in their chart, who presented for any clinical visit including asthma were administered ACT. The staff scored the ACT and included the form in the encounter sheet so that the physicians can review the scores, address the asthma control, severity, and document in the chart. The number of patients whose asthma control was assessed improved from 10% per year to 85% after the three PDSA cycles. Administration of the tool did not impact the flow of the patients in a busy primary care practice. Screening asthma severity and control for patients diagnosed with asthma with a validated questionnaire when presenting for any chief complaint including asthma will help the provider address the severity and control of asthma symptoms in a timely manner and would potentially help prevent unwanted emergency department or urgent care usage.